THE CONCEPT OF NŪR MUḤAMMAD IN “MAULID AD-DĪBA‘Ī”: A SCHLEIERMACHERIAN HERMENEUTIC PERSPECTIVE - Fina Mazida Husna; Muhyar Fanani; Mowafg Masuwd; Nely Irnik Darajah (CMES (Center of Middle Eastern Studies), 2025)
This study aims to uncover the hidden meaning within the concept of Nūr Muḥammad as found in the Maulid ad-Dība‘ī, a classical Arabic literary work by ‘Abd ar-Raḥmān of Yemen, widely popular in Indonesia. Schleiermacher’s hermeneutics, which consists of grammatical and psychological interpretation, is employed as the analytical framework. Grammatical interpretation is conducted by examining the structure and linguistic choices in the text to uncover implicit meanings, while psychological interpretation delves into the author’s inner context through his biography, intellectual background, and spiritual environment. Utilizing a qualitative approach based on library research, the findings reveal that, grammatically, the concept of Nūr Muḥammad in Maulid ad-Dība‘ī is positioned as a primordial light that predates all prophets, including Prophet Ādam, and serves as a manifestation of the nobility of the Prophet Muḥammad. Psychologically, ad-Dība‘ī presents Muhammad not merely within a historical framework but also as the center of human existence and spirituality. More than a Sufi concept, Nūr Muḥammad in this work functions as a theological symbol that represents profound reverence for the Prophet and serves as a spiritual medium that radiates wisdom to those whose hearts are purified through love and the emulation of Muhammad.